2017
DOI: 10.1111/jdv.14671
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous immunoglobulin administration on erythrocyte and leucocyte parameters

Abstract: IVIG products should be administered strictly according to indications. Commercially available IVIG products can contain blood group-specific antibodies that may induce haemolysis in some recipients. Monitoring of blood counts during applied IVIG therapy, especially when high doses are administered, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 37 publications
0
24
0
8
Order By: Relevance
“…Additional mechanisms, such as apoptosis or other cell death pathways, may also be involved, and we cannot exclude an effect of the IVIG treatment, as reported previously in some studies. 23,27,28,30,31 Compared with children with acute infection, most of the individuals with postacute hyperinflammation received IVIG treatment before sampling, some combined with glucocorticosteroids. The immunosuppressive effects of glucocorticoids are identified at the cytokine/chemokine level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional mechanisms, such as apoptosis or other cell death pathways, may also be involved, and we cannot exclude an effect of the IVIG treatment, as reported previously in some studies. 23,27,28,30,31 Compared with children with acute infection, most of the individuals with postacute hyperinflammation received IVIG treatment before sampling, some combined with glucocorticosteroids. The immunosuppressive effects of glucocorticoids are identified at the cytokine/chemokine level.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in some cases, IVIG treatment could impair DC function and decrease monocyte and DC proportions. 23,25,[27][28][29][30][31] In addition, some heterogeneity was observed in the proportions of non-classical monocytes in Acute-Inf (CoV-2 + ) cases and additional heterogeneity in the proportions of classical and intermediate monocytes in individuals with severe myocarditis (MIS-C_MYO (CoV-2 + )) (Figures 3A and 3B), but there was no correlation with clinical data, including treatments, age (Table S1), and cytokine/chemokine measurements (Figures 2 and S2). Additional modifications were detected in individuals with acute SARS-CoV-2 infection (Acute-Inf (CoV-2 + ) cases), consisting of a decrease in mucosal-associated invariant T cells (MAIT) and an excess of naive and central memory CD4 + T cells (Figures 3A, 3B, S3C, and S3D).…”
Section: Low Monocyte and Dendritic Cell Frequencies In Individuals With Postacute Hyperinflammatory Illnessmentioning
confidence: 99%
“…Neutropenia following IVIG therapy has been observed in case reports and series of neurological, hematological, and pediatric patients [20][21][22][23][24][25][26][27][28][29]. To the best of our knowledge, data on IVIG-induced hematological side effects in dermatological cohorts are restricted to a recent case series by Cicha et al [30]. Guidelines regarding the use of IVIG in dermatology fail to give advice on IVIG-related neutropenia [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Fallserien aus der Neurologie, Hämatologie und Pädiatrie wird außerdem über Neutropenien während und nach Gabe von IVIG berichtet [20][21][22][23][24][25][26][27][28][29]. Nach unserem Kenntnisstand beschränken sich Daten zu hämatologischen Nebenwirkungen der IVIG-Therapie bei dermatologischen Patienten auf eine 2018 durch Cicha et al publizierte Fallserie [30]. Das Risiko einer Neutropenie wird in aktuellen Leitlinien zum dermatologischen Einsatz von IVIG nicht thematisiert [9].…”
Section: Introductionunclassified
“…Nach unserem Kenntnisstand beschränken sich Daten zu hämatologischen Nebenwirkungen der IVIG‐Therapie bei dermatologischen Patienten auf eine 2018 durch Cicha et al. publizierte Fallserie [30]. Das Risiko einer Neutropenie wird in aktuellen Leitlinien zum dermatologischen Einsatz von IVIG nicht thematisiert [9].…”
Section: Introductionunclassified